2020
DOI: 10.1158/2159-8290.cd-19-1008
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP and CD39 Activate cAMP-Mediated Mitochondrial Stress Response to Promote Cytarabine Resistance in Acute Myeloid Leukemia

Abstract: Relapses driven by chemoresistant leukemic cell populations are the main cause of mortality for patients with acute myeloid leukemia (AML). Here, we show that the ectonucleotidase CD39 (ENTPD1) is upregulated in cytarabine (AraC)-resistant leukemic cells from both AML cell lines and patient samples in vivo and in vitro. CD39 cell surface expression and activity is increased in AML patients upon chemotherapy compared to diagnosis and enrichment in CD39-expressing blasts is a marker of adverse prognosis in the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…We next investigated the function of CD39 in HCC. Recent studies have observed a high level of CD39 in tumor-infiltrating immune cells from many tumors [ 12 , 24 , 25 ]. Some tumors including kidney, lung, testicular, and thyroid tumor cells, but not HCC, express a high level of CD39 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the function of CD39 in HCC. Recent studies have observed a high level of CD39 in tumor-infiltrating immune cells from many tumors [ 12 , 24 , 25 ]. Some tumors including kidney, lung, testicular, and thyroid tumor cells, but not HCC, express a high level of CD39 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study found that the expression level of P2RY13 in LUAD tissues was downregulated. However, previous studies reported that P2RY13 expression in acute myeloid leukemia was increased, and regulated cyclic adenosine monophosphate-mediated cytarabine resistance ( Aroua et al, 2020 ; Maiga et al, 2016 ). To date, there is no basic research on the role of P2RY13 in LUAD, nor studies on the role of P2RY13 on the TME or immune reactions in LUAD.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, our studies suggested the multifunctional roles of ATP as an energy supplier facilitating drug efflux and a signaling transducer activating signaling pathways related to cell survival and resistance, drug efflux and tumor migration/invasion. eATP can also contribute to cancer drug resistance as an extracellular messenger through P2 purinergic signaling, which is composed of nucleotides/nucleosides (mainly ATP and adenosine) acting as signaling ligands with their corresponding membrane receptors and modulating diverse signaling pathways [206] . There are two P2 receptor families: P2X receptors which are ATP-gated ion channels and P2Y receptors which are mainly activated by ATP or ADP.…”
Section: Atp and Atp-mediated Drug Resistancementioning
confidence: 99%
“…There are two P2 receptor families: P2X receptors which are ATP-gated ion channels and P2Y receptors which are mainly activated by ATP or ADP. P2X and P2Y family members emerge as players in resistance to chemotherapies [ 207 , 208 ] . Ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1, or CD39) eATPase activity, which converts eATP to AMP, coordinately activated mitochondrial stress response via the downstream P2RY13/cAMP/PKA axis and promoted cytarabine resistance by enhancing mitochondrial OXPHOS activity in acute myeloid leukemia (AML).…”
Section: Atp and Atp-mediated Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation